Safe and sound: examining the effect of a training targeting psychological safety and trust in peer assessment - Senden, Morgane; De Jaeger, Dominique; Coertjens, Liesje (Frontiers in Education, 2023)
Peer feedback can be very beneficial for student learning in higher education, yet students may feel uncomfortable providing and receiving peer feedback: they may for example not feel safe in the group or have little trust in their peers’ abilities to provide feedback. Surprisingly, only few studies have investigated how students’ feelings of discomfort can be reduced. To fill this gap, we created a 1-hour training session using active learning methods. The training focuses on enhancing students’ perceptions of psychological safety, trust in their abilities and in their peers’ abilities to provide feedback, relying on recommendations by Blanchard and Thacker (2012). The efficacy of this training was tested using a quasi-experiment with pre- and post-test design. Second-year bachelor students in physical education participated in a peer feedback activity to fulfill the requirement of an obligatory course. In 2019-2020, 47 students participated in a peer assessment activity without specific training on psychological safety and trust (control group), while in 2021-2022, 42 students received specific training before peer assessment (experimental group). Analyses include a comparison of the control and experimental groups with regard to (1) the evolution of their perceptions (psychological safety, trust in their abilities, and trust in their peers’ abilities) for pre- to post-test, (2) the quality of the feedback they provided to their peers (3) and the improvement of students’ work between the draft submitted for the peer activity and the final version submitted to the professor. Results do not support the training’s efficacy, yet suggest pathways for future research.